Chemical Characteristics, Glycemic Index, and Glycemic Load of Instant Potato Cream Soup with Quail Egg Flour, Tempeh, Soy Protein Isolate - Wulan Dari, Dini; Sulaeman, Ahmad; Setiawan, Budi; Zuraidah Nasution (Indonesian Food Science and Technology Journal, 2026)
Managing blood glucose levels by selecting foods with a low glycemic index (GI) and glycemic load (GL) is important in preventing and controlling metabolic diseases such as diabetes mellitus. This study aimed to determine the chemical characteristics, GI, and GL of four instant potato cream soup formulations using quail egg flour, tempeh, and soy protein isolate (ISP) as additives. Adding these ingredients aims to increase the product's nutritional content and modify its glycemic response. This study used an experimental design with a complete randomized design (CRD). The results showed that adding tempeh, ISP, and quail egg flour increased the products' protein and dietary Fiber proportion. The GI values of the four products were low. High GI values were found in the control formulation (SK0) and SK1 (tempeh addition). Formulations with the addition of ISP (SK2) and SK3, as well as tempeh, ISP, and quail egg flour, produced medium-category GL and have the potential to support more effective blood glucose management. In conclusion, this modification has potential in the development of innovative functional food products based on natural ingredients that are healthier and suitable for blood sugar management, as well as supporting the prevention of metabolic diseases.